Bio-Based Graphene From The Oil Palm Empty Fruit Bunches As A Fluid Loss Additive In The Water-Based Drilling Mud - Safian, Muhammad Taqi-Uddeen (2024)
One of the most serious issues encountered during drilling operations is the loss of drilling fluid through the well formation, which is referred to as fluid loss, resulting in dry drilling fluid and increasing the likelihood of the drill being stuck. To prevent this scenario, a fluid loss additive was added to the drilling mud. The effectiveness of bio-based graphene (BG) prepared from oil palm (Elaeis guineensis) empty fruit bunches biomass as a fluid loss additive for water-based drilling mud (WBM) was investigated. To accomplish this, BG was exfoliated from lignin extracted through a soda pulping process. The BG exfoliation process consisted of a combination of thermal treatment via pyrolysis at 300, 600, 800, and 1000 °C with a reaction time of 60 minutes under an argon atmosphere, followed by a mechanical exfoliation using a homogenizer with a shear rate of 12400 rpm for 1 hour. Ultraviolet-visible spectroscopy (UV-Vis), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), and x-ray photoelectron spectroscopy (XPS) were used to characterize each prepared sample. The Raman analysis confirmed the graphene formation based on the I2D/IG value similar to the commercial graphene, i.e., 0.91. The FTIR analysis revealed that the BG structure has a less functional group than GO, which has been confirmed using XPS as the C/O ratio of BG is less than GO.